Development and Feasibility of an Android-Based Interactive Media for Learning Tahsin and Tajwid - Nurliansyah, Muhammad Zulfikri; Aziz, Muhammad Thariq; Saepuloh, Luthpi (Research, Training and Philanthropy Institution Natural Aceh, 2025)
The integration of digital media into the learning process has become an important alternative for improving teaching quality and student engagement, especially when traditional methods face limitations in time and interactivity. This study aims to develop an Android-based interactive learning medium for Tahsin and Tajwid using the Research and Development (R&D) method through the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The developed product was tested on tenth-grade students at SMK Muhammadiyah 1 Sukabumi and validated by experts in media, content, and language to ensure its quality and functionality. The results showed that the learning media achieved a feasibility score above 85%, placing it in the “highly feasible” category. The “Ngetahsin” application proved effective in improving students’ understanding, motivation, and engagement in learning Tahsin and Tajwid. Theoretically, this study contributes to the development of Islamic educational technology through multimedia-based mobile learning. Practically, it offers a relevant digital solution to strengthen Quranic literacy and support more effective, engaging religious education for students.